The measurement of proprioceptive accuracy: A systematic literature review - Áron Horváth; Eszter Ferentzi; Kristóf Schwartz; Nina Jacobs; Pieter Meyns; Ferenc Köteles (Elsevier, 2023)
Background: Proprioceptive accuracy refers to the individual's ability to perceive proprioceptive information, that is, the information referring to the actual state of the locomotor system, which originates from mechanoreceptors located in various parts of the locomotor system and from tactile receptors located in the skin. Proprioceptive accuracy appears to be an important aspect in the evaluation of sensorimotor functioning; however, no widely accepted standard assessment exists. In this systematic review, our goal was to identify and categorize different methods that are used to assess different aspects of proprioceptive accuracy. Methods: A literature search was conducted in 5 different databases (PubMed, SPORTDiscus, PsycINFO, ScienceDirect, and SpringerLink). Results: Overall, 1139 scientific papers reporting 1346 methods were included in this review. The methods assess 8 different aspects of proprioception: (a) the perception of joint position, (b) movement and movement extent, (c) trajectory, (d) velocity, and the sense of (e) force, (f) muscle tension, (g) weight, and (h) size. They apply various paradigms of psychophysics (i.e., the method of adjustment, constant stimuli, and limits). Conclusion: As the outcomes of different tasks with respect to various body parts show no associations (i.e., proprioceptive accuracy is characterized by site-specificity and method-specificity), the appropriate measurement method for the task needs to be chosen based on theoretical considerations and/or ecological validity.